A process for efficiently treating cold rolling chromium-containing wastewater
Through the composite materials and multi-step process of divalent iron doped nanotitanium dioxide and other materials, the problem of hexavalent chromium removal in cold-rolled chromium-containing wastewater is solved, efficient chromium reduction and purification is achieved, and treatment costs and pollutant generation is reduced.
Patent Information
- Application Number
- CN202411230199.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Cold-rolled chromium-containing wastewater treatment is difficult to effectively remove hexavalent chromium, and the existing chemical reduction precipitation methods have problems such as many types of pollutants, complex components and low treatment efficiency.
The composite material is prepared by mixing divalent iron-doped nanotitanium dioxide, sodium borohydride, polyimide and sodium sulfite. Combined with a multi-step process of grid filtration, ceramic membrane and modified nanofiltration membrane, and removed by chemical reduction and physical filtration. Hexavalent chromium and use ozone to sterilize emission standards.
It has achieved efficient reduction of hexavalent chromium to trivalent chromium, reduced the chromium content, improved the purification effect and treatment efficiency of wastewater, reduced the generation of pollutants, and met the requirements of sustainable development.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment and relates to a process for efficiently treating cold-rolling chromium-containing wastewater. Background Art
[0002] Cold rolling wastewater is one of the most difficult wastewaters to treat in the metallurgical industry due to the large variety of pollutants, complex composition, and large changes in water volume and composition. However, with the continuous increase in demand, more and more rolled steel surfaces are subjected to chrome plating processes. While product quality has improved, it has also brought about the problem of treating chromium-containing wastewater. As we all know, heavy metal chromium, especially hexavalent chromium, is highly toxic and is a swallowed / inhaled poison. It can invade the human body through the digestive tract, respiratory tract, skin, and mucous membranes, and accumulate in the human body and the environment, causing hereditary genetic defects and even carcinogenicity, and has lasting harm to the environment. Therefore, the treatment of cold rolling chromium-containing wastewater is particularly important.
[0003] Chemical reduction precipitation is the earliest and most widely used method for treating chromium-containing wastewater at home and abroad. This treatment technology generally uses sulfuric acid to adjust the pH value of the wastewater to an acidic condition of 2-3, then uses a chemical reducing agent to reduce the hexavalent chromium in the solution to trivalent chromium, and then uses sodium hydroxide or lime milk to adjust the pH value to 7-9 to generate insoluble trivalent chromium precipitates that are separated from the water body to achieve the purpose of chromium removal. Summary of the invention
[0004] The purpose of the present invention is to provide a process for efficiently treating cold rolling chromium-containing wastewater, which has the characteristics of high wastewater treatment efficiency.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A process for efficiently treating cold rolling chromium-containing wastewater, the specific process of the process is as follows:
[0007] S1: Collect wastewater and filter it through a screen to remove large particles and sediments;
[0008] S2: Collect the wastewater after coarse filtration, pass it into the regulating tank to balance the water quality and adjust the water volume, add the composite material to the wastewater, and stir for 1 hour;
[0009] S3: passing the waste liquid obtained in S2 into a neutralization tank to generate chromium hydroxide precipitation, and then using a ceramic membrane for the first filtration;
[0010] S4: filtering the wastewater treated in S3 for a second time through a modified nanofiltration membrane to obtain a clear liquid;
[0011] S5: passing ozone into the clear liquid obtained in S4 for sterilization, and discharging the treated waste liquid;
[0012] The preparation method of the composite material in S2 is as follows:
[0013] S2.1: dissolving ferrous chloride in deionized water to prepare a ferrous chloride solution with a mass fraction of 30-50%, adding nano-titanium dioxide into the ferrous chloride solution, wherein the mass ratio of nano-titanium dioxide to ferrous chloride is (1-4):3, to obtain a solid-liquid mixture A;
[0014] S2.2: The solid-liquid mixture A is heated to 60°C, stirred at a speed of 200 r / min for 1 hour, allowed to stand at 60°C for 2 hours, then slowly cooled to room temperature, filtered, dried at 80°C for 10 hours, calcined in a nitrogen atmosphere for 2 hours after drying, and ground after calcination to obtain a mixture B;
[0015] S2.3: Sodium borohydride, polyimide and sodium sulfite are mixed in a mass ratio of 2:1:1, and ground in a ball mill at a speed of 400 r / min to obtain a mixture C;
[0016] S2.4: Mix mixture B and mixture C in a mass ratio of 1:1, add 3-5 wt% of polyethylene glycol with a number average molecular weight of 400, grind at room temperature at a speed of 300 r / min for 0.5 h to obtain mixture D, dry mixture D at 80°C for 12 h, and then calcine at 400°C for 4 h to obtain the composite material.
[0017] Furthermore, in S3, a sodium hydroxide solution with a mass fraction of 10% is added to the neutralization tank to carry out a neutralization reaction.
[0018] Furthermore, the pore size of the ceramic membrane in S3 is 4-8 nm.
[0019] Furthermore, the modified nanofiltration membrane preparation method in S4 is as follows:
[0020] S4.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution E with a mass fraction of 20%;
[0021] S4.2: Mixing the graphene oxide solution E and a 50% by mass m-phenylenediamine aqueous solution in a volume ratio of 1:1 to obtain a mixed solution F;
[0022] S4.3: Soak the Kevlar fiber in the mixed solution F for 12 hours at a temperature of 40° C. After soaking, dry the fiber at room temperature to obtain the modified nanofiltration membrane.
[0023] Furthermore, the flow pressure of the nanofiltration membrane in S4 is 0.25~1MPa.
[0024] Furthermore, the ozone is introduced into S5 at a flow rate of 10 m / s and for a time of 2 h.
[0025] Furthermore, the rate of slowly cooling from 60°C to room temperature in S2.2 is 2°C / min.
[0026] Furthermore, the particle size of the mixture B obtained by grinding in S2.2 is 150 mesh.
[0027] In the present invention, nano titanium dioxide doped with divalent iron, sodium borohydride, polyimide and sodium sulfite are mixed to prepare a composite material, which is used to treat chromium-containing wastewater, mainly for the removal and reduction of hexavalent chromium. Through the synergistic effect of multiple components in the composite material, the hexavalent chromium in the wastewater can be effectively reduced to trivalent chromium with lower toxicity, and removed from the wastewater by precipitation.
[0028] The divalent iron-doped nano-titanium dioxide in the composite material has excellent catalytic reduction performance and can efficiently remove hexavalent chromium in wastewater. Ferrous ions can undergo redox reaction with hexavalent chromium in wastewater to reduce it to trivalent chromium. The polyimide in the composite material can act as a stabilizer, thereby improving the stability and service life of the composite material. The treatment process does not produce secondary pollution and meets the requirements of sustainable development.
[0029] Nano-titanium dioxide doped with divalent iron can generate photogenerated electrons and holes under light conditions. These photogenerated electrons have strong reducing properties and can reduce hexavalent chromium in wastewater to trivalent chromium. Sodium borohydride and sodium sulfite, as strong reducing agents, can directly reduce hexavalent chromium in wastewater. In addition, they may also promote the generation and transfer of photogenerated electrons on the surface of nano-titanium dioxide, thereby enhancing the photocatalytic reduction effect. There is also a synergistic effect between the components in the composite material. The photocatalytic effect of nano-titanium dioxide can promote the reduction reaction of sodium borohydride and sodium sulfite. At the same time, the intermediate products produced by the reduction reaction may further promote the photocatalytic reaction. The synergistic effect between the substances further improves the treatment efficiency of the composite material for chromium-containing wastewater.
[0030] The present invention uses a modified nanofiltration membrane to further improve the efficiency and purification effect of wastewater treatment, reduce the chromium content in the wastewater, and make it meet the discharge standard;
[0031] Graphene oxide has excellent physical and chemical properties, such as high specific surface area, excellent mechanical strength and chemical stability. Introducing graphene oxide into nanofiltration membranes can increase the porosity and selectivity of the membranes and improve the retention capacity of the membranes.
[0032] In the preparation process of the present invention, graphene oxide can be combined with Kevlar fiber through the cross-linking agent m-phenylenediamine by physical adsorption and chemical bonding to form a stable composite membrane structure. As a cross-linking agent, m-phenylenediamine can undergo a cross-linking reaction with graphene oxide and Kevlar fiber, and its amino group and the oxygen-containing functional group hydroxyl and carboxyl of graphene oxide will undergo a condensation reaction and produce hydrogen bonding to form a stable chemical bond or intermolecular force, forming a dense membrane structure, and this cross-linking effect not only enhances the mechanical strength of the membrane, but also improves the stability and anti-pollution performance of the membrane.
[0033] The present invention selects Kevlar fiber as the substrate, which provides a good supporting structure and mechanical strength for the nanofiltration membrane, prolongs the service life of the membrane, reduces the frequency of maintenance and replacement, and reduces the operating cost.
[0034] The present invention first performs coarse filtration through a grid, effectively removing large particle impurities and sediments in the wastewater, providing good conditions for subsequent treatment steps, and reducing the wear and clogging risks of treatment equipment; the wastewater after coarse filtration is passed into a regulating tank to balance the water quality and water quantity. This step ensures the stability and consistency of the wastewater during subsequent treatment and improves the overall treatment efficiency. Adding the composite material to the equalization tank and stirring it for 1 hour helps to further improve the water quality of the wastewater and remove harmful substances in the wastewater through chemical reactions and physical adsorption. The wastewater is passed into the neutralization tank to react the chromium ions in the wastewater with the added chemical reagents to generate chromium hydroxide precipitates. The first filtration is performed using a ceramic membrane to further remove suspended matter and sediments in the wastewater, including the generated chromium hydroxide precipitates, thereby improving the cleanliness of the wastewater. The second filtration is performed using a modified nanofiltration membrane to more efficiently remove tiny pollutants such as soluble organic matter and heavy metal ions in the wastewater, further improving the treatment effect of the wastewater. Finally, ozone is introduced into the treated clear liquid for sterilization and disinfection, which effectively removes pathogenic and harmful microorganisms in the wastewater and ensures the safety and harmlessness of discharged wastewater.
[0035] Beneficial effects of the present invention:
[0036] The present invention mixes nano titanium dioxide doped with divalent iron, sodium borohydride, polyimide and sodium sulfite to prepare a composite material. Through the synergistic effect of multiple components in the composite material, hexavalent chromium in wastewater can be effectively reduced to trivalent chromium with lower toxicity, and removed from the wastewater by precipitation.
[0037] The present invention uses Kevlar fiber as a substrate, combines graphene oxide by physical adsorption and chemical bonding to form a stable composite membrane structure, further improves the efficiency and purification effect of wastewater treatment, reduces the chromium content in wastewater, and makes it meet the discharge standard;
[0038] The present invention ensures the environmental protection and high efficiency of the treatment process by combining the steps of grid, regulating tank, ceramic membrane, modified nanofiltration membrane and ozone sterilization, reduces the energy consumption and material consumption in the treatment process and reduces the treatment cost through reasonable process design and operation control. DETAILED DESCRIPTION
[0039] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0040] Example 1
[0041] S1: Collect wastewater and filter it through a screen to remove large particles and sediments;
[0042] S2: Collect the wastewater after coarse filtration, pass it into the regulating tank to balance the water quality and adjust the water volume, add the composite material to the wastewater, and stir for 1 hour;
[0043] S3: The waste liquid obtained in S2 is passed into a neutralization tank, and a sodium hydroxide solution with a mass fraction of 10% is added to generate chromium hydroxide precipitation, and then a ceramic membrane is used for the first filtration, and the pore size of the ceramic membrane is 6nm;
[0044] S4: The wastewater treated in S3 is filtered for a second time through a modified nanofiltration membrane, the flow pressure of the nanofiltration membrane is 0.25 MPa, and a clear liquid is obtained after filtration;
[0045] S5: introducing ozone into the clear liquid obtained in S4 for sterilization, the ozone introduction flow rate is 10 m / s, the introduction time is 2 h, and the treated waste liquid is discharged;
[0046] The preparation method of the composite material in S2 is as follows:
[0047] S2.1: dissolving ferrous chloride in deionized water to obtain a ferrous chloride solution with a mass fraction of 50%, adding nano-titanium dioxide into the ferrous chloride solution, wherein the mass ratio of nano-titanium dioxide to ferrous chloride is 2:3, to obtain a solid-liquid mixture A;
[0048] S2.2: The solid-liquid mixture A is heated to 60°C, stirred at a speed of 200 r / min for 1 hour, and after the stirring is completed, it is allowed to stand at 60°C for 2 hours, and then slowly cooled to room temperature at a rate of 2°C / min, filtered, dried at 80°C for 10 hours, and then calcined in a nitrogen atmosphere for 2 hours after drying. After the calcination is completed, it is ground to obtain a mixture B, and the particle size of the mixture B is 150 mesh;
[0049] S2.3: Sodium borohydride, polyimide and sodium sulfite are mixed in a mass ratio of 2:1:1, and ground in a ball mill at a speed of 400 r / min to obtain a mixture C;
[0050] S2.4: Mix mixture B and mixture C in a mass ratio of 1:1, add 4 wt% of polyethylene glycol with a number average molecular weight of 400, grind at room temperature at a speed of 300 r / min for 0.5 h to obtain mixture D, dry mixture D at 80°C for 12 h, and then calcine at 400°C for 4 h to obtain the composite material.
[0051] The modified nanofiltration membrane preparation method in S4 is as follows:
[0052] S4.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution E with a mass fraction of 20%;
[0053] S4.2: Mixing the graphene oxide solution E and a 50% by mass m-phenylenediamine aqueous solution in a volume ratio of 1:1 to obtain a mixed solution F;
[0054] S4.3: Soak the Kevlar fiber in the mixed solution F for 12 hours at a temperature of 40° C. After soaking, dry the fiber at room temperature to obtain the modified nanofiltration membrane.
[0055] Example 2
[0056] S1: Collect wastewater and filter it through a screen to remove large particles and sediments;
[0057] S2: Collect the wastewater after coarse filtration, pass it into the regulating tank to balance the water quality and adjust the water volume, add the composite material to the wastewater, and stir for 1 hour;
[0058] S3: The waste liquid obtained in S2 is passed into a neutralization tank, and a sodium hydroxide solution with a mass fraction of 10% is added to generate chromium hydroxide precipitation, and then a ceramic membrane is used for the first filtration, and the pore size of the ceramic membrane is 4nm;
[0059] S4: The wastewater treated in S3 is filtered for a second time through a modified nanofiltration membrane, the flow pressure of the nanofiltration membrane is 1 MPa, and a clear liquid is obtained after filtration;
[0060] S5: introducing ozone into the clear liquid obtained in S4 for sterilization, the ozone introduction flow rate is 10 m / s, the introduction time is 2 h, and the treated waste liquid is discharged;
[0061] The preparation method of the composite material in S2 is as follows:
[0062] S2.1: dissolving ferrous chloride in deionized water to obtain a ferrous chloride solution with a mass fraction of 30-50%, adding nano-titanium dioxide into the ferrous chloride solution, wherein the mass ratio of nano-titanium dioxide to ferrous chloride is 4:3, to obtain a solid-liquid mixture A;
[0063] S2.2: The solid-liquid mixture A is heated to 60°C, stirred at a speed of 200 r / min for 1 hour, and after the stirring is completed, it is allowed to stand at 60°C for 2 hours, and then slowly cooled to room temperature at a rate of 2°C / min, filtered, dried at 80°C for 10 hours, and then calcined in a nitrogen atmosphere for 2 hours after drying. After the calcination is completed, it is ground to obtain a mixture B, and the particle size of the mixture B is 150 mesh;
[0064] S2.3: Sodium borohydride, polyimide and sodium sulfite are mixed in a mass ratio of 2:1:1, and ground in a ball mill at a speed of 400 r / min to obtain a mixture C;
[0065] S2.4: Mix mixture B and mixture C in a mass ratio of 1:1, add 3 wt % of polyethylene glycol with a number average molecular weight of 400, grind at room temperature at a speed of 300 r / min for 0.5 h to obtain mixture D, dry mixture D at 80° C. for 12 h, and then calcine at 400° C. for 4 h to obtain the composite material.
[0066] The modified nanofiltration membrane preparation method in S4 is as follows:
[0067] S4.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution E with a mass fraction of 20%;
[0068] S4.2: Mixing the graphene oxide solution E and a 50% by mass m-phenylenediamine aqueous solution in a volume ratio of 1:1 to obtain a mixed solution F;
[0069] S4.3: Soak the Kevlar fiber in the mixed solution F for 12 hours at a temperature of 40° C. After soaking, dry the fiber at room temperature to obtain the modified nanofiltration membrane.
[0070] Example 3
[0071] S1: Collect wastewater and filter it through a screen to remove large particles and sediments;
[0072] S2: Collect the wastewater after coarse filtration, pass it into the regulating tank to balance the water quality and adjust the water volume, add the composite material to the wastewater, and stir for 1 hour;
[0073] S3: The waste liquid obtained in S2 is passed into a neutralization tank, and a sodium hydroxide solution with a mass fraction of 10% is added to generate chromium hydroxide precipitation, and then a ceramic membrane is used for the first filtration, and the pore size of the ceramic membrane is 8nm;
[0074] S4: The wastewater treated in S3 is filtered for a second time through a modified nanofiltration membrane, the flow pressure of the nanofiltration membrane is 0.6 MPa, and a clear liquid is obtained after filtration;
[0075] S5: introducing ozone into the clear liquid obtained in S4 for sterilization, the ozone introduction flow rate is 10 m / s, the introduction time is 2 h, and the treated waste liquid is discharged;
[0076] The preparation method of the composite material in S2 is as follows:
[0077] S2.1: dissolving ferrous chloride in deionized water to prepare a ferrous chloride solution with a mass fraction of 30-50%, adding nano-titanium dioxide into the ferrous chloride solution, wherein the mass ratio of nano-titanium dioxide to ferrous chloride is 1:3, to obtain a solid-liquid mixture A;
[0078] S2.2: The solid-liquid mixture A is heated to 60°C, stirred at a speed of 200 r / min for 1 hour, and after the stirring is completed, it is allowed to stand at 60°C for 2 hours, and then slowly cooled to room temperature at a rate of 2°C / min, filtered, dried at 80°C for 10 hours, and then calcined in a nitrogen atmosphere for 2 hours after drying. After the calcination is completed, it is ground to obtain a mixture B, and the particle size of the mixture B is 150 mesh;
[0079] S2.3: Sodium borohydride, polyimide and sodium sulfite are mixed in a mass ratio of 2:1:1, and ground in a ball mill at a speed of 400 r / min to obtain a mixture C;
[0080] S2.4: Mix mixture B and mixture C in a mass ratio of 1:1, add 5 wt% of polyethylene glycol with a number average molecular weight of 400, grind at room temperature at a speed of 300 r / min for 0.5 h to obtain mixture D, dry mixture D at 80°C for 12 h, and then calcine at 400°C for 4 h to obtain the composite material.
[0081] The modified nanofiltration membrane preparation method in S4 is as follows:
[0082] S4.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution E with a mass fraction of 20%;
[0083] S4.2: Mixing the graphene oxide solution E and a 50% by mass m-phenylenediamine aqueous solution in a volume ratio of 1:1 to obtain a mixed solution F;
[0084] S4.3: Soak the Kevlar fiber in the mixed solution F for 12 hours at a temperature of 40° C. After soaking, dry the fiber at room temperature to obtain the modified nanofiltration membrane.
[0085] Comparative Example 1
[0086] In this comparative example, the titanium dioxide is not doped with divalent iron during the preparation of the composite material, and the remaining steps are consistent with those in Example 1.
[0087] Comparative Example 2
[0088] In this comparative example, sodium borohydride was not added in the preparation of the composite material, and the remaining steps were consistent with those in Example 1.
[0089] Comparative Example 3
[0090] In this comparative example, polyimide was not added in the preparation of the composite material, and the remaining steps were consistent with those in Example 1.
[0091] Comparative Example 4
[0092] In this comparative example, no sodium sulfite was added during the preparation of the composite material, and the remaining steps were consistent with those of Example 1.
[0093] Comparative Example 5
[0094] In this comparative example, the nanofiltration membrane was not modified, and the remaining steps were consistent with those in Example 1.
[0095] The chromium content of the discharged waste liquid was tested according to GB 8978-1996 standard for the embodiments and comparative examples. The experimental results are summarized in the following table:
[0096]
[0097] Experimental data show that the addition of composite materials and the modification of nanofiltration membranes have improved the treatment efficiency of chromium-containing wastewater.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for efficiently treating cold rolling chromium-containing wastewater, characterized in that: The specific process of the process is as follows: S1: Collect wastewater and filter it through a screen to remove large particles and sediments; S2: Collect the wastewater after coarse filtration, pass it into the regulating tank to balance the water quality and adjust the water volume, add the composite material to the wastewater, and stir for 1 hour; S3: passing the waste liquid obtained in S2 into a neutralization tank to generate chromium hydroxide precipitation, and then using a ceramic membrane for the first filtration; S4: The wastewater treated in S3 is filtered for a second time through a modified nanofiltration membrane to obtain a clear liquid. The passing pressure of the nanofiltration membrane is 0.25~1MPa; The modified nanofiltration membrane preparation method is as follows: S4.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution E with a mass fraction of 20%; S4.2: Mixing the graphene oxide solution E and a 50% by mass m-phenylenediamine aqueous solution in a volume ratio of 1:1 to obtain a mixed solution F; S4.3: soaking the Kevlar fiber in the mixed solution F for 12 hours at a temperature of 40° C., and drying at room temperature to obtain the modified nanofiltration membrane; S5: passing ozone into the clear liquid obtained in S4 for sterilization, and discharging the treated waste liquid; The preparation method of the composite material in S2 is as follows: S2.1: dissolving ferrous chloride in deionized water to prepare a ferrous chloride solution with a mass fraction of 30-50%, adding nano-titanium dioxide into the ferrous chloride solution, wherein the mass ratio of nano-titanium dioxide to ferrous chloride is (1-4):3, to obtain a solid-liquid mixture A; S2.2: The solid-liquid mixture A is heated to 60°C, stirred at a speed of 200 r / min for 1 hour, and after stirring, allowed to stand at 60°C for 2 hours, and then slowly cooled to room temperature at a rate of 2°C / min, filtered, dried at 80°C for 10 hours, and then calcined in a nitrogen atmosphere for 2 hours after drying. After calcination, the mixture is ground to obtain a mixture B. The particle size of the ground mixture B is 150 mesh; S2.3: Sodium borohydride, polyimide and sodium sulfite are mixed in a mass ratio of 2:1:1, and ground in a ball mill at a speed of 400 r / min to obtain a mixture C; S2.4: Mix mixture B and mixture C in a mass ratio of 1:1, add 3-5 wt% of polyethylene glycol with a number average molecular weight of 400, grind at room temperature at a speed of 300 r / min for 0.5 h to obtain mixture D, dry mixture D at 80°C for 12 h, and then calcine at 400°C for 4 h to obtain the composite material.
2. A process for efficiently treating cold rolling chromium-containing wastewater according to claim 1, characterized in that: In S3, a sodium hydroxide solution with a mass fraction of 10% is added to the neutralization tank to carry out a neutralization reaction.
3. A process for efficiently treating cold rolling chromium-containing wastewater according to claim 1, characterized in that: The pore size of the ceramic membrane in S3 is 4-8 nm.
4. A process for efficiently treating cold rolling chromium-containing wastewater according to claim 1, characterized in that: The ozone in S5 has an introduction velocity of 10 m / s and an introduction time of 2 h.
Citation Information
Patent Citations
High-concentration chromium-containing wastewater treatment method capable of reducing sludge output
CN112811663A
Preparation method of homogeneous fiber reinforced PPTA hollow fiber nanofiltration membrane
CN115532077A